Students in Economics Facing a Digital Divide - Joshi, Bishnu Maya (Molung Educational Frontier, 2023)
The digital divide in schools in developing countries is becoming increasingly evident as information communication and technology (ICT) has entered the educational system. However, access to ICT infrastructure alone does not guarantee that a person would be motivated to use it. The unequal access to digital technology is a digital divide. In Nepal, the COVID-19 pandemic caused limited access to ICT among low-income families and rural populations. This research aimed to inquire into the motivational access-based digital divide among12 students in economics in Kathmandu Valley. The research problem of this study was: what are the ICT access levels for Class 12 economics students in Kathmandu Valley regarding motivational access? The researcher utilized a descriptive study design under quantitative methodology for the study. Closed structured questionnaires were used to collect primary data. Descriptive analysis is included in the analysis of data. It is used to calculate the percentage, frequency, mean, and standard deviation to assess the motivational access level of students through the Likert-scale data. The study's findings demonstrated a digital divide among students regarding motivational access. There is no distinct difference between the students regarding school type (private and community).The digital divide between gender, rural and urban origin, ethnicity, and parents ‘employment conditions is evident. This study implies that parents and concerned authorities should provide favorable environments to increase motivational access to ICT, which reduces the digital divide in terms of motivational access.